Revisiting Orthopaedic Surgery Residents’ Views of the CDC and AAOS Precautionary Guidelines for HIV - Schwarzman, Garrett (JB JS Open Access, 2018)
BACKGROUND: The purpose of the present study was to evaluate how orthopaedic residents’ views and behaviors toward the human immunodeficiency virus (HIV) have changed over the past 25 years. METHODS: Between May 2017 and June 2017, an electronic survey was distributed to residents who were enrolled orthopaedic residency programs in the United States. The survey included questions based on the revised 2012 American Academy of Orthopaedic Surgeons (AAOS) and Centers for Disease Control and Prevention (CDC) guidelines for HIV, hepatitis B virus (HBV), and hepatitis C virus (HCV) transmission prevention. Every program in the United States was contacted to avoid selection bias. Categorical data were analyzed with use of the chi-square goodness-of-fit test for the comparison of current and historical results. The null hypothesis of no change between survey results in 1992 and 2016 was set at p > 0.05. Numerical data were analyzed with use of the chi-square goodness-of-fit test with subsequent p value calculations to determine deviation from expected values between the 2 study years. RESULTS: The present study demonstrated that there have been compelling changes in residents’ attitudes and behaviors with respect to HIV. Current residents are more aware of and compliant with their institutional safety protocols. They are also more accepting of treating HIV-positive patients. However, current residents underestimate the risk of HIV transmission from needle-stick injury and are less aware of proper timing for post-exposure prophylactic medication administration. CONCLUSIONS: The present study indicates that there has been a compelling positive change in perception and prevention of HIV transmission by orthopaedic residents in the past 25 years but that there is still room for improvement.